Fracture resistance of class IV fiber-reinforced composite resin restorations: An in vitro study - P S Praveen Kumar; K T Srilatha; B Nandlal (Wolters Kluwer Medknow Publications, 2017)
Objectives: The aim of this study was to evaluate fracture resistance of incisal edge fractures (Class IV) restored with a Glass Fiber-reinforced Composite (FRC). Materials and Methods: Twenty-four extracted sound maxillary central incisors were randomly divided into two groups. Group I (control) contained untreated teeth. Samples in experimental groups II were prepared by cutting the incisal (one-third) part of the crown horizontally and was subjected to enamel preparations, then restored with a Glass FRC. Fracture resistance was evaluated as Newton's for samples tested in a Hounsfield universal testing machine. Failure modes were examined microscopically. Results: Mean peak failure load (Newton's) observed in Glass Fiber-reinforced Nanocomposite was 863.50 ± 76.12. The experimental group showed similar types of failure modes with the majority occurring as cohesive and mixed type. 58% of the teeth in Glass FRC group fractured below the cementoenamel junction. Conclusion: Using Fiber reinforced composite substructure under conventional composites in Class IV restorations, the fracture resistance of the restored incisal edge could be increased.